An Analysis of the Cost-Effectiveness of Spinal Versus General Anesthesia for Lumbar Spine Surgery in Various Hospital Settings. Issue 4 (June 2019) - Morris, Matthew T.; Morris, Jonathan; Wallace, Camari; Cho, Woojin; Sharan, Alok; Abouelrigal, Manal; Joseph, Vilma
Study Design: Retrospective chart review. Objective: To determine the relative cost-effectiveness of spinal anesthesia and general anesthesia for lumbar laminectomy and microdiscectomy surgery performed in an academic versus private practice hospital setting. Methods: The authors retrospectively reviewed charts of 188 consecutive patients who underwent lumbar laminectomy or microdiscectomy by a single surgeon from 2012 to 2016 at either an academic or a private practice hospital setting. Intraoperative and postoperative outcomes were recorded and direct variable costs were calculated. Results: At the academic institution, the direct cost of a lumbar laminectomy or microdiscectomy surgery under general anesthesia was determined to be 9.93% greater than with spinal anesthesia ( P = .040). The greatest difference was seen with operating room costs, in which general anesthesia was associated with 18.74% greater costs than spinal anesthesia ( P = .016). There was no significant difference in cost at the private practice hospital setting. Conclusions: We conclude that use of spinal anesthesia for lumbar laminectomy leads to less operating room, postanesthesia care unit, and anesthesia times, lower levels of postoperative pain, and no increased rate of other complications compared with general anesthesia at an academic institution as compared to a private practice setting. Spinal anesthesia is 9.93% less expensive than general anesthesia, indicating substantial cost-saving potential. With no sacrifice of patient outcomes and the added benefit of less pain and recovery time, Spinal anesthesia represents a more cost-effective alternative to general anesthesia in lumbar spine surgery in the academic hospital setting.